Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Bantuan Scaffolding Kognitif Terhadap Keterampilan Menulis Ilmiah dan Hasil Belajar Siswa SMP - Supeno; Arista Eka kumalasari (UNIB Press, 2026)
The current state of junior high school students' scientific writing skills and learning outcomes is still low due to the dominance of teacher-oriented learning models. This study aims to examine the effect of a guided inquiry learning model with cognitive scaffolding on junior high school students' scientific writing skills and learning outcomes in science learning. The approach used was quantitative with a quasi-experimental method and a non-equivalent posttest-only control group design. Purposive sampling was used to select samples, including two classes: the experimental class and the control class. Data analysis was carried out through three test phases: normality testing, homogeneity testing, and hypothesis testing. The data showed that the experimental class obtained a higher average score than the control class. This is evidenced by a significance value of 0.000, which is smaller than the 0.05 threshold, indicating that the implementation of a guided inquiry learning model with cognitive scaffolding has a significant effect on students' scientific writing skills and learning outcomes.